Platelet indices and inflammatory bowel disease: a Mendelian randomization study - Li, Hong-yang; Liu, Tie-mei (Frontiers in Immunology, 2024)
Background Platelets play a significant role in the innate and adaptive processes of immunity and inflammation. Inflammatory bowel disease (IBD) is an autoimmune disease that is widely understood to be caused by a combination of genetic predisposition, aberrant immune responses, etc. Methods To examine the relationships between genetically determined platelet indices and IBD, we conducted a Mendelian randomization (MR) study. Data associated with platelet count (PLT), mean platelet volume (MPV), platelet distribution width (PDW), plateletcrit (PCT) were used from the UK Biobank. The outcome data, including IBD, Crohn’s disease (CD), ulcerative colitis (UC), were from the FinnGen database. The inverse variance-weighted (IVW), MR-Egger, weighted median methods were used for MR analyses. Results The MR estimations from the IVW approach show a significant connection between PLT and IBD. Similarly, PCT and IBD have a relationship following the IVW and MR-Egger approaches. While PLT and PCT have strong relationships with CD, according to the findings of all three approaches respectively. Nevertheless, PDW was the only relevant indicator of UC. The only significant result was IVW’s. Conclusion Our findings suggest that the fluctuation of platelet indicators is of great significance in the development of IBD. PLT and PCT have a close association with IBD and CD, respectively; PDW only has a connection with UC. Platelets play an important role in the progression of IBD (UC, CD).